Arbeitsunfall 4.0 Die Abgrenzung privater und beruflicher Risikosphären in der modernen Arbeitswelt - Aumann, Annemarie (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2019)
Digitisation and tertiarisation have made it difficult to categorise activities as private or work-related. The two notions that have traditionally been used to make that distinction - i.e. place of work and working time - are losing their importance. An increasing number of employees are subject to the phenomenon of blurred boundaries: They set their own hours, work from home or on-the-go. German Social Accident Insurance, however, determines the question of coverage on the allocation of the accident to either the work sphere or the private sphere of the aggrieved party. The book explores the extent to which it is necessary to modernise the way risks are allocated in order to not discriminate against those who have jobs outside of traditional parameters and discusses whether it is still adequate to base allocation mechanisms on the principles of the employers' business risk and duties of care. By way of extensive dogmatic analysis and a comparison with other systems of risk allocation, the study proposes a modern take on allocating risks with just results for both employers and employees from all fields of work.